Escapism Towards the Surreal Arena in Negeri Senja: A Literary Psychology Approach - Nina Dwi Hapsari Putri; Edi Dwi Riyanto (Hasanuddin University, 2022)
“Negeri Senja” tells the story of a country that never has morning, noon, or night because there is only dusk every day. The surreal arena built into the story brings anxiety during the reading process even to the end of the open ending. The problems in this novel are framed textually. This research aims to express these concerns based on textual analysis of the novel “Negeri Senja” by Seno Gumira Ajidarma. The research method used is literary psychology, specifically Carl Gustav Jung's psychoanalysis of consciousness and unconsciousness. Content and discussion are presented in the form of qualitative descriptive analysis. The results of the textual study show that the main character in the story is undergoing a process of escapism or attitude that avoids reality and avoids all difficulties. The surreal arena in the form of “Negeri Senja” is interpreted as the center of the main character's escapism so that all reading concerns can be explained.